ITO thin films for low-resistance gas sensors - Almaev, Aleksei V.; Kopyev, Viktor V.; Novikov, Vadim A.; Chikiryaka, Andrei V.; Yakovlev, Nikita N.; Usseinov, Abay B.; Karipbayev, Zhakyp T.; Akilbekov, Abdirash T.; Koishybayeva, Zhanymgul K.; Popov, Anatoli I. (Materials)
Indium tin oxide thin films were deposited by magnetron sputtering on ceramic aluminum nitride substrates and were annealed at temperatures of 500 °C and 600 °C. The structural, optical, electrically conductive and gas-sensitive properties of indium tin oxide thin films were studied. The possibility of developing sensors with low nominal resistance and relatively high sensitivity to gases was shown. The resistance of indium tin oxide thin films annealed at 500 °C in pure dry air did not exceed 350 Ohms and dropped by about 2 times when increasing the annealing temperature to 100 °C. Indium tin oxide thin films annealed at 500 °C were characterized by high sensitivity to gases. The maximum responses to 2000 ppm hydrogen, 1000 ppm ammonia and 100 ppm nitrogen dioxide for these films were 2.21 arbitrary units, 2.39 arbitrary units and 2.14 arbitrary units at operating temperatures of 400 °C, 350 °C and 350 °C, respectively. These films were characterized by short response and recovery times. The drift of indium tin oxide thin-film gas-sensitive characteristics during cyclic exposure to reducing gases did not exceed 1%. A qualitative model of the sensory effect is proposed.